Severity of self-reported symptoms and psychological burden 6-months after hospital admission for COVID-19: a prospective cohort study. (November 2021) - ELOY, Philippine; TARDIVON, Coralie; MARTIN-BLONDEL, Guillaume; ISNARD, Margaux; TURNIER, Paul LE; MARECHAL, Marion LE; CABIÉ, André; LAUNAY, Odile; TATTEVIN, Pierre; SENNEVILLE, Eric; ANSART, Séverine; GOEHRINGER, François; et al.
Abstract: Objectives: Few studies have reported clinical COVID-19 sequelae six months (M6) after hospital discharge, but none has studied symptom severity. Methods: Prevalence and severity of 7 symptoms were estimated until M6 using the self-administered influenza severity scale in COVID-19 hospitalized patients enrolled in the French COVID cohort. Factors associated with severity were assessed by logistic regression. Anxiety, depression and health-related quality of life (HRQL) were also assessed. Results: At M6, among the 324 patients (median age 61 years, 63% men, 19% admitted to intensive care during the acute phase), 187/324 (58%) reported at least one symptom, mostly fatigue (47%) and myalgia (23%). Symptom severity was scored, at most, mild in 125 (67%), moderate in 44 (23%) and severe in 18 (10%). Female gender was the sole factor associated with moderate/severe symptom reporting (OR = 1.98, 95%CI=1.13-3.47). Among the 225 patients with psychological assessment, 24 (11%) had anxiety, 18 (8%) depressive symptoms, and their physical HRQL was significantly poorer than the general population (p=0.0005). Conclusion: Even if 58% of patients reported ≥1 symptom at M6, less than 7% rated any symptom as severe. Assessing symptoms severity could be helpful to identify patients requiring appropriate medical care. Women may require special attention.